IMPACT OF MATERNAL KNOWLEDGE AND EMPLOYMENT ON EXCLUSIVE BREASTFEEDING IN BELU, EAST NUSA TENGGARA - Sebayang, Elisabet Br; Atika, Atika; Frety, Endyka Erye; Sampurna, Mahendra Arif (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
According to the Belu District Health Service, exclusive breastfeeding rates for babies aged 0-6 months at the Atapupu Community Health Center decreased in 2021. This research aims to determine the relationship between maternal knowledge, employment, and exclusive breastfeeding. The study uses a cross-sectional design. Data were collected from the Atapupu Health Center, Belu Regency, NTT (June-July 2022), involving 70 participants. This research employed a total sampling technique. Primary and secondary data were gathered using questionnaires, and the data were analyzed using the Chi-Square statistical test. Results from the univariate analysis indicated that regarding knowledge about exclusive breastfeeding, nearly 26 respondents (37.1%) had sufficient knowledge. In terms of mothers' employment, the majority worked as housewives, with 49 respondents (62.9%). Additionally, 42 respondents (60%) were more likely to practice exclusive breastfeeding. The Chi-Square test results showed a significant relationship between maternal knowledge and exclusive breastfeeding, with a p-value of 0.001 (p 0.05) and an odds ratio (OR) of 0.6, indicating a relationship between knowledge and exclusive breastfeeding. Conversely, the relationship between maternal employment and exclusive breastfeeding yielded a p-value of 0.099 (p 0.05), suggesting no significant relationship between employment and exclusive breastfeeding.